Srdce nevymeníš : (Szívet cserélni nehéz) - Egri, Viktor: 1898-1982; Ličková, Marta: 1926-; Smrek, Ján: 1898-1982; Kočiš, Jaroslav: 1933-1990; Šmatláková-Mančíková, Elena: 1926-1987 (Mladé letá, 1962)
Kto chce mať novú vlasť, musí si vymeniť aj srdce...